Beyond barbarity and concealment: animal sacrifice and religious slaughter in Islamic responses to postdomesticity. Issue 3 (2nd July 2016) - Dahlan-Taylor, Magfirah
Abstract: In a society where animals to be consumed as food are produced using modern industrial animal farming system (described as postdomestic in Bulliet [2005 ]), most people who consume animals are very much removed from the production process. Most consumers do not participate actively or have intimate knowledge of the rearing and slaughtering of animals for food. In this article, I critically analyse existing Islamic responses to problems arising from the postdomestic condition with regard to consuming animal as food. In this article, my analysis focuses on making explicit the connection between the assumption of barbarity in the civilising discourse surrounding religious requirement for animal slaughter and the problem of postdomestic concealment of animals we consume. Furthermore, I analyse the role that the Islamic requirement for animal slaughter ( zabiha ) and the tradition of Festival of Sacrifice ( eid al - adha ) can have potential solutions that religion can offer to the problems of postdomesticity.